2019
DOI: 10.3831/kpi.2019.22.028
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chamomile in the Treatment of Premenstrual Syndrome: A Systematic Review

Abstract: Premenstrual syndrome (PMS) encompasses a vast array of physical and psychological symptoms. Of the herbal supplements mentioned for remedy PMS symptoms, chamomile used as an effective herbal medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
0
18
0
4
Order By: Relevance
“…Additionally, clinical studies demonstrated that M. chamomilla could exhibit an interesting analgesic effect on women during childbirth [182,183]. The plant was also efficient in relieving the pain of mild to moderate mastalgia, breast pain often preceding the menstrual period [184]. In addition, some reviews gathered studies on the use of M. chamomilla in the treatment of premenstrual syndrome [185], primary dysmenorrhea, and reducing menstrual bleeding [186].…”
Section: Phyotherapeutical Applicationsmentioning
confidence: 99%
“…Additionally, clinical studies demonstrated that M. chamomilla could exhibit an interesting analgesic effect on women during childbirth [182,183]. The plant was also efficient in relieving the pain of mild to moderate mastalgia, breast pain often preceding the menstrual period [184]. In addition, some reviews gathered studies on the use of M. chamomilla in the treatment of premenstrual syndrome [185], primary dysmenorrhea, and reducing menstrual bleeding [186].…”
Section: Phyotherapeutical Applicationsmentioning
confidence: 99%
“…The diagnostic criteria of the PMS for affective symptoms and somatic symptoms must be experienced during the five days before menses in three prior menstrual cycles and relieved with the menstrual flow [ 7 ]. The primary psychological range of PMS is anxiety and depression [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is higher in women who experience PMS as per the previous research [ 5 ]. Consequently, as an etiology is unclear, several possible treatments are prescribed and purchased [ 8 ]. Various therapeutic interventions have been scientifically confirmed helpful in PMS ranging from nonpharmacological management (cognitive behavioral therapy, lifestyle modification and diet, education, exercise, and complementary and herbal medications) to pharmacotherapy hormonal therapy (gonadotropin-releasing hormone (GnRH) agonists OCP, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations